Manajemen Ekstrakurikuler Drumband di SMPN 15 Mataram - Regita, Fenty; Rifqi, Ainur (Edu Learning : Journal of Education and Learning, 2024)
This research discusses the management of extracurricular drumband at SMPN 15 Mataram. This research is a type of qualitative research. Data collection in this study through interviews, observations and documentation studies using data analysis techniques in the form of data condensation, data presentation, and conclusion drawing. The location of this research is SMPN 15 Mataram, Mataram City, Lombok, West Nusa Tenggara. The results of this study indicate that (1) The planning of extracurricular drumband is carried out by compiling a work program consisting of weekly, monthly and annual work programs, compiling budgeting plans and planning extracurricular drumband infrastructure. (2) Organizing extracurricular drumband is done by conducting a selection to select prospective members for extracurricular drumband and creating an organizational structure for extracurricular drumband. (3) The implementation of extracurricular drumband is carried out with the stages of morning gymnastics, taking drumband learning instruments, drumband practice in the field, prayer, and evaluation. (4) Evaluation of drumband extracurricular activities is carried out weekly and monthly. This extracurricular drumband management provides benefits for students, namely being able to increase the potential talents and interests of students in music, besides that in this extracurricular drumband activity also teaches students about discipline.